2021
DOI: 10.1002/ange.202016592
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Self‐sorting of Giant Cubic [8+12] Salicylimine Cage Compounds

Abstract: Chiral self-sorting is intricately connected to the complicated chiral processes observed in nature and no artificial systems of comparably complexity have been generated by chemists.H owever,o nly af ew examples of purely organic molecules have been reported so far,w here the selfsorting process could be controlled. Herein, we describe the chiral self-sorting of large cubic [8+ +12] salicylimine cage compounds based on ac hiral TBTQ precursor.O ut of 23 possible cage isomers only the enantiopure and am eso ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 118 publications
0
15
0
1
Order By: Relevance
“…The positive influence of aromatic solvents on the catenation process is poorly understood and may be linked to solvation effects [34] . In dichloromethane an ( M )‐ 4 /( M )‐ 3 ratio of 12 : 88 was observed (Table 1, Entry 2), while in a previous publication we reported only the formation of single cage ( M )‐ 3 ; [23] a difference that can be explained by the fact, that the reaction conditions in this experiment were optimized for catenation (see Chapter 11 of the Supporting Information). The highest ( M )‐ 4 /( M )‐ 3 ratio of 92 : 8 was observed in toluene (Table 1, Entry 13).…”
Section: Resultsmentioning
confidence: 83%
“…The positive influence of aromatic solvents on the catenation process is poorly understood and may be linked to solvation effects [34] . In dichloromethane an ( M )‐ 4 /( M )‐ 3 ratio of 12 : 88 was observed (Table 1, Entry 2), while in a previous publication we reported only the formation of single cage ( M )‐ 3 ; [23] a difference that can be explained by the fact, that the reaction conditions in this experiment were optimized for catenation (see Chapter 11 of the Supporting Information). The highest ( M )‐ 4 /( M )‐ 3 ratio of 92 : 8 was observed in toluene (Table 1, Entry 13).…”
Section: Resultsmentioning
confidence: 83%
“…We investigated the influence of a large number of aliphatic and aromatic solvents on the catenation process by MALDI‐TOF mass spectrometry and 1 H NMR spectroscopy (Scheme 1 and Table 1; for details see Chapter 12 of the Supporting Information). Since preliminary experiments had shown that an excess of the amine linker 2 favors the formation of catenane (see Chapter 11 of the Supporting Information), a small excess of amine (4 % over the stoichiometric ratio) was used in all reactions [23] . The solvents in Table 1 are listed in order of decreasing polarity according to their normalized empirical solvent polarity parameters normalETnormalN ${{{\rm { E}}}_{{\rm { T}}}^{{\rm { N}}}}$ [33] .…”
Section: Resultsmentioning
confidence: 99%
“…Such chiral self‐sorting has been examined through two distinct options: dynamic covalent chemistry and coordination‐driven self‐assembly. The former involves reversible bond‐forming organic reactions under thermodynamic control, wherein a significant control over the choice of chiral self‐sorting outcome has been established in higher‐order complex structures [4–7] . Differently functionalized ligands, such as bidentate catechols, [8,9] 2,2‐bipyridines [10] and imino‐2‐pyridines [11–13] with octahedral metal centers, and monodentate bis‐pyridines with square‐planar Pd(II) ions were examined with a later approach [14–19] .…”
Section: Introductionmentioning
confidence: 99%